Correction of Asian Short Nose with Lower Lateral Cartilage Repositioning and Ear Cartilage Grafting - Jin Suk Byun, MD, PhD; Kenneth K. Kim, MD, FACS (Plastic and Reconstructive Surgery, Global Open, 2013)
Background: Asians with short nose lack the cartilage needed to extend the length of the nose. A rhinoplasty technique using lower lateral cartilage (LLC) repositioning and ear cartilage grafting allows for sufficient nasal lengthening and nasal tip mobility in the correction of short nose in Asians. Methods: Short nose was classified into 3 subtypes: type I, II, or III. During LLC repositioning, the LLC was separated from surrounding retaining structures, except at the footplate. The LLC was approximated medially and advanced with a Medpor strut. A silicone dorsal implant was inserted to suit the newly projected nasal tip. An ear cartilage onlay graft or ear cartilage extension graft was applied to further project and enhance the nasal tip and columella. Results: Of the 854 primary rhinoplasty procedures performed on Asian patients between January 2008 and December 2011, 295 were performed on patients with short nose. LLC repositioning and ear cartilage onlay grafting were performed on 228 patients. LLC repositioning and ear cartilage extension grafting with or without ear cartilage onlay grafting were performed on 67 patients. Short nasal tip, alar retraction, and columellar retraction were corrected. Wound dehiscence with marginal necrosis occurred in 7 patients. One patient developed nasal infection. Conclusions: LLC repositioning and ear cartilage grafting aid in the correction of short nose in Asians. With LLC repositioning and ear cartilage grafting, the nasal tip can be positioned in accordance with the patient’s anatomic limits. The entire nasal tip and columella can be lengthened, while the tip maintains its mobility.